Impact of modulating surface heat flux through sea ice leads on Arctic sea ice in EC-Earth3 in different climates - T. Tian; R. Davy; L. Ponsoni; S. Yang (The Cryosphere)
This sensitivity study examines the impact of modulating surface sensible heat flux over leads – open-water areas within sea ice cover – to approximate finer-scale processes that are often underrepresented in climate models. We aim to assess how this parameterization (referred to as ECE3L) influences the persistent positive bias in Arctic sea ice (concentration and thickness) in the global climate model EC-Earth3 (ECE3). We performed two pairs of 50-year simulations using 1985 (cold-climate) and 2015 (warm-climate) forcing, with the latter characterized by thinner ice and weaker atmospheric boundary layer stability during winter. Our results show that modified heat flux alters surface air temperatures in the Arctic, with minimal impact on lower latitudes. The changes are more pronounced in the cold-climate experiment, particularly during Arctic winter. We also performed a historical ensemble comparison between ECE3L and ECE3 over a transient-climate period (1980–2014). We found that the spatial patterns in mean sea ice changes in the transient climate closely resembled those observed in the cold-climate experiment. However, the reduction in the total sea ice area and volume in ECE3L relative to ECE3 was nearly 4 times greater in the cold climate compared with the transient climate. This suggests that amplified heat flux through leads is less effective in a warming climate with decreasing winter stratification. Notably, ECE3L shows closer alignment with observational data and refines the declining sea ice volume trend overestimation in ECE3, reducing overestimated ensemble variability caused by excessive sea ice. This, in turn, amplifies sea ice sensitivity to Arctic warming, particularly in the marginal ice zone. These findings emphasize the importance of accurately representing surface heat flux through sea ice leads, which plays a critical role in capturing the influence of atmospheric stability on sea ice dynamics and regional Arctic amplification.